2003
DOI: 10.1007/s00296-003-0381-5
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in patients with Beh�et?s disease

Abstract: Behçet's disease is a complex, multisystemic, inflammatory disorder characterized clinically by recurrent oral and genital ulcerations as well as uveitis, sometimes leading to blindness. The etiology and pathogenesis of this syndrome remain obscure. However, various factors are suspected, including genetic propensity, infectious precipitants, and immunological abnormalities. Considering the chronicity and unclear etiology of the disease, we conducted a prospective investigation of a possible alteration in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 11 publications
1
19
2
Order By: Relevance
“…Bicer et al found and reported no significant differences between control and BD patients. 2 Kirnap et al reported significant difference in bone mineral density, T score and scores of L2-L4, but not in other region. 3 We found significant difference in all regions of BMD measurements except L2-L4 vertebra BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bicer et al found and reported no significant differences between control and BD patients. 2 Kirnap et al reported significant difference in bone mineral density, T score and scores of L2-L4, but not in other region. 3 We found significant difference in all regions of BMD measurements except L2-L4 vertebra BMD.…”
Section: Discussionmentioning
confidence: 99%
“…1 In several studies, it was shown that bone involvement, particularly osteoporosis and osteopenia, is commonly developed in BD due to natural course of disease and agents used for its treatment. 2,3 Osteoporosis is considered to be an imbalance of the remodeling process, in which bone resorption exceeds bone formation. A growing understanding of this process has shown that factors involved in inflammation are linked to critical factors associated with bone physiology.…”
Section: Introductionmentioning
confidence: 99%
“…The chronicity and vasculitic background of the disease and the drugs for the treatment of BD suggest that bone metabolism might be affected negatively, which then leads to bone loss, resulting in osteoporosis in patients with BD [8]. Osteoporosis is a common disease characterized by a systemic impairment of bone mass and microarchitecture that causes fragility fractures [39].…”
Section: Bone Metabolismmentioning
confidence: 99%
“…There are limited numbers of clinical trial that reveal the status of bone metabolism and bone mineral density (BMD) in the medical literature, and findings in these investigations are in consistent [8, 19, 46]. First, the status of BMD was investigated in a study, where BMD measurements of lumbar spine and hip in BD showed similar results when compared to those in healthy subjects [8].…”
Section: Bone Metabolismmentioning
confidence: 99%
See 1 more Smart Citation